Essential newborn care practices and associated factors among home delivered mothers in Damot pulasa Woreda, southern Ethiopia - Tesfaye Yitna Chichiabellu; Baze Mekonnen; Feleke Hailemichael Astawesegn; Birhanu Wondimeneh Demissie; Antehun Alemayehu Anjulo (BMC, 2018)
Abstract Background Globally 3.1 million children die each year in their neonatal period (first 28 days of life) according to World Health Organization (WHO) 2011 report. Half of these surprisingly occur within the first 24 h of delivery and 75% occur in the early neonatal period. Methods A community based cross-sectional study design was carried out from March 2016 to April, 2016 in Damot Pulasa district, Wolaita zone, Southern Ethiopia to assess selected essential newborn care practices and associated factors among home delivered mothers in Damot pulasa district. Data were entered into Epi Info version 3.5.1 and exported to SPSS version 20 software for analysis. Multiple logistic analyses were done to control possible confounding variable. A P-value less than 0.05 was taken as a significant association. Result The study showed that the prevalence of essential newborn care practice was 24%. Multivariate logistic regression analysis revealed that variables like ANC visit (AOR =0.213,P = 0.015,CI = 0.102-0.446),PNC visit (AOR = 0.209, P = 0.00,CI = 0.110-0.399), advice about essential newborn care practice (AOR =0.114,P = 0.0001, CI = 0.058-0.221),urban areas women (AOR =2,P = 0.042, CI = 1.024-3.693), planned pregnancy (AOR = 7, P = 0.00, CI =3.732-11.813), and knowledge about newborn danger signs (AOR = 0.277, P = 0.006, CI = 0.110-0.697) were the independent predictors of ENBC practices. Conclusion Generally, coverage of essential newborn care practices was low. ANC visit, advice about ENBC, PNC visit, residence, planned pregnancy and knowledge about newborn danger signs were predictors of essential newborn care practice in the study area. Therefore, Health facilities should enhance linkage with health posts to increase ANC and PNC service utilization. Health extension workers should also promote and give health education about pre-lacteal feeding, early bathing, planned pregnancy, newborn danger signs and application of materials on the newborn stump.